The Use of Technetium-99m Radioactive Isotope in The Diagnosis and Treatment of Thyroid Diseases: A Review - Shlair I. Mohammed (Al-Kitab Journal for Pure Sciences)
A Tc-99m thyroid scanning is one of the most common diagnostic modalities in nuclear medicine for the evaluation of various thyroid dysfunctions and anomalies. Therefore, this review study will delve into the various dimensions related to patient exposure during Tc-99m thyroid scanning. Various subjects are covered, such as radiation risks from the procedure, methods for reducing patient exposures, imaging technology developments, and the importance of an effective radiation safety program. In this review, some new developments in and possible ways toward better safety for the patient and diagnostic accuracy of the thyroid imaging methods are also discussed.